2011
DOI: 10.1097/hco.0b013e328345af13
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular assist device unloading effects on myocardial structure and function: current status of the field and call for action

Abstract: Purpose of review Myocardial remodeling driven by excess pressure and volume load is believed to be responsible for the vicious cycle of progressive myocardial dysfunction in chronic heart failure. Left ventricular assist devices (LVADs), by providing significant volume and pressure unloading, allow a reversal of stress-related compensatory responses of the overloaded myocardium. Herein, we summarize and integrate insights from studies which investigated how LVAD unloading influences the structure and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 114 publications
(105 reference statements)
1
77
0
2
Order By: Relevance
“…Bruggink et al 43 demonstrated a biphasic response with an initial increase in fibrosis, followed by a subsequent regression with prolonged LVAD therapy (after 200 days of support). Drakos et al 7,46 with advanced image analysis found higher interstitial and total fibrosis in failing hearts and that the collagen content increased further after LVAD unloading.…”
Section: Circulation Research August 30 2013mentioning
confidence: 99%
“…Bruggink et al 43 demonstrated a biphasic response with an initial increase in fibrosis, followed by a subsequent regression with prolonged LVAD therapy (after 200 days of support). Drakos et al 7,46 with advanced image analysis found higher interstitial and total fibrosis in failing hearts and that the collagen content increased further after LVAD unloading.…”
Section: Circulation Research August 30 2013mentioning
confidence: 99%
“…Continuous flow LVADs (CF‐LVADs) have been shown to improve mortality, morbidity, functional status, and quality of life in patients with advanced HF 2, 3, 4. Ventricular arrhythmias, however, are commonly seen in patients with LVAD,5, 6, 7 and the vast majority of LVAD recipients who had implantable cardioverter defibrillators (ICDs) continue to receive ICD therapies post‐LVAD implant 8.…”
mentioning
confidence: 99%
“…the left ventricle relieved by this pump system. Although histopathological evaluation of cardiac apex in these circumstances might represent a useful adjunct for further assessment of prognosis and planning of treatment strategies for patients on an individual base, there are only very limited data on this aspect in the clinical and pathological cardiology literature [7,8]. To our knowledge, only two studies have analysed this in more details [9,10].…”
Section: Introductionmentioning
confidence: 99%